FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN PROMOTIF DI PUSKESMAS SIMALINGKAR TAHUN 2018 - Hartono, Hartono -; Ginting, Clara E. P. (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2018)
Puskesmas is a health service facility that organizes public health efforts and first-degree individual health efforts, prioritizing promotive and preventif efforts to achieve the highest degree of public health in their working area. Promotive health efforts are efforts aimed at improving health. Promotive services at Simalingkar Community Health Center still have not reached the targets set in each section, namely environmental health, nutrition, health promotion, MCH / family planning, prevention and control of infectious diseases. This study aims to determine the factors that influence the quality of promotive service in Simalingkar Health Center in 2018. The design of this study was an analytical survey with a cross sectional study design. The total population of the study was 25 people. The sampling technique used is total sampling, that is all populations are used as research samples. Data collection techniques through direct interviews using a questionnaire. The method of data analysis was carried out by univariate, bivariate and multivariate analysis (fisher test and chi-square test) with a significance level of p-value = 0.05. The results of data analysis obtained p-value of health care performance 0.030 (p-value <0.05), facilities and infrastructure 0.027 (p-value <0.05), and community participation 0.116 (p-value> 0.05). It was concluded that there was a relationship between the performance of health workers and infrastructure on the quality of promotive services while the participation of the community had no relationship to the quality of promotive services. It is hoped that the related government can complete the facilities and infrastructure needed in promotive services and for the Head of the Puskesmas to increase the motivation to improve the performance of officers such as increasing knowledge and skills, collaboration among officers, task resolution, work motivation and personality in order to achieve promotive services quality.